A new species of Delma Gray 1831 (Squamata: Pygopodidae) from the Hunter Valley and Liverpool Plains of New South Wales - Mahony, Stephen V.; Cutajar, Timothy; Rowley, Jodi J.l. (Zootaxa, 2022)
The Striped Legless Lizard Delma impar Fischer 1882 occurs in grasslands of south-eastern Australia where it is sometimes sympatric with several congeners. Previous molecular analyses have revealed mitochondrial divergence between the northern and southern lineages of D. impar, but the status of a recently detected population assigned to the species in the Hunter Valley of New South Wales (NSW), 250 km north of other populations, remains unknown. Via morphological and molecular analyses across the known distribution of D. impar, we distinguish the population from the Hunter Valley, Liverpool Plains region as a unique taxon and describe this species as D. vescolineata sp. nov. The new species is divergent from D. impar in both nuclear and mitochondrial analysis, and differing facial scalation and colour patterning from the limited number of specimens available. The degree of mitochondrial and nuclear divergence between the previously identified northern and southern clades of D. impar is consistent with a single species. This is the first description of a Delma from south-eastern Australia since 1974, but the second new vertebrate taxon identified from the Hunter Valley region within a decade. Our research highlights our incomplete understanding of the biodiversity of the Hunter Valley region, despite its relative proximity to populous areas. The range of D. vescolineata sp. nov. is restricted and heavily overlaps with major habitat modification including mining and grazing, with no parks or reserves in this distribution protecting the species’ grassland habitat. Gathering more data to understand conservation status of this species should be a priority.